Discordance of Diagnostic Core Biopsy and Final Histopathology Performed after Surgical Resection of Breast Cancer - Khan, Said Zaman; Qamar, Syeda Rifaat; Nadeem, Muhammad Sohaib; Khan, Ayesha; Mushtaq, Afroz; Jan, Maria Mir (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of discordance of receptor status in our breast cancer patients, find out its causes, and suggest remedial measures.Study Design: Retrospective longitudinal study.Place and Duration of Study: Breast clinic and Radiation Oncology Department of Combined Military Hospital Rawalpindi Pakistan from Jan 2018 to Nov 2021.Methodology: Estrogen Receptor, Progesterone Receptor and Her2 Neu status differences between diagnostic tru-cut biopsy and surgical specimen were compared.Results: Receptor status between initial core biopsy and final histopathology of 63 patients were compared. Discordance rates of 05 (7.90%), 13 (20.60%) and 12 (19%) were noted for Estrogen receptor, progesterone receptor and Her2, respectively. The highest discordance noted was for the progesterone receptor, followed by the HER2 receptor and the Estrogen receptor.Conclusion: The highest discordance noted was for the progesterone receptor, followed by the HER2 receptor and the Estrogen receptor. Further studies are required to know more about the causes of receptor status discordance, its impact on treatment decisions and its impact on disease progression and survival.